Detection of SARS-CoV-2-Specific Humoral and Cellular Immunity in COVID-19 Convalescent Individuals - Ni, Ling; Ye, Fang; Cheng, Meng-Li; Feng, Yu; Deng, Yong-Qiang; Zhao, Hui; Wei, Peng; Ge, Jiwan; Gou, Mengting; Li, Xiaoli; Sun, Lin; Cao, Tianshu; et al. (Immunity (Cambridge, Mass.), 2020)
The World Health Organization has declared SARS-CoV-2 virus outbreak a worldwide pandemic. However, there is very limited understanding on the immune responses, especially adaptive immune responses to SARS-CoV-2 infection. Here, we collected blood from COVID-19 patients who have recently become virus-free, and therefore were discharged, and detected SARS-CoV-2-specific humoral and cellular immunity in eight newly discharged patients. Follow-up analysis on another cohort of six patients 2 weeks post discharge also revealed high titers of immunoglobulin G (IgG) antibodies. In all 14 patients tested, 13 displayed serum-neutralizing activities in a pseudotype entry assay. Notably, there was a strong correlation between neutralization antibody titers and the numbers of virus-specific T cells. Our work provides a basis for further analysis of protective immunity to SARS-CoV-2, and understanding the pathogenesis of COVID-19, especially in the severe cases. It also has implications in developing an effective vaccine to SARS-CoV-2 infection.